PERANAN PENDIDIKAN LUAR SEKOLAH DALAM PEMBANGUNAN BERWAWASAN LINGKUNGAN - Ishak . G Bactiar (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2007)
The environmental problems become interesting issues in Indonesia nowadays. A lot of recent natura environmental dangers have worried the government and the people. This article discusses the roles of education, particularly out of school; education, in educating people to be alert of these environmental problems and actively participates in protecting the natural environment. Out of school education is considered effective in shifting the paradigm of Indonesia citizens about the natural environmental and changing the destructive attitude to be constructive behavior.